Primary Pulmonary Adenocarcinoma in a Cow - de Andrade Neto, Adony Querubino; Souto, Rodolfo José Cavalcanti; Cajueiro, Jobson Filipe de Paula; de Mendonça, Carla Lopes; Driemeier, David; de Almeida Souza, José Claudio; Mendonça, Fábio de Souza; Bastos Afonso, José Augusto (Acta Scientiae Veterinariae, 2019)
Background: Primary neoplasms of the respiratory tract are rare in cattle, and they present with nonspecific clinical signs and are usually found at post-mortem. Pulmonary adenocarcinoma of the acinar type is uncommon, and information about this neoplasm in cattle is scarce. This paper aims to describe the clinical, laboratory, and pathological findings in a cow with this neoplasm. Case: A 10-year-old, adult, mixed-breed Holstein cow weighing 300 kg was referred to the Garanhuns Cattle Clinic of the Campus of Federal Rural University of Pernambuco, Brazil, with a history of decreased appetite, tiredness, weight loss, and difficulty in breathing for two months. The animal had been treated at the farm of origin with enrofloxacin, florfenicol, and flunixin meglumine. The animal’s appetite improved, but no improvement in the respiratory symptoms was observed. On examination at our center, the cow was in an orthopedic position, with neck extension and elbow abduction; and it remained in a recumbent position. The cow had neutrophilia, normochromic normocytic anemia, and hyperfibrinogemia. The body condition score (BCS) was 1 (BCS ranges from 1 to 5), and the cow had moderate enophthalmia, serous secretions in nostrils, tachycardia, and tachypnea. It also had increased breathing intensity; increased breath sounds in the cranial regions of both lungs; areas of reduced breath sounds in the medial portions of the lungs; intermittent wheezing in the cranial region of the left lung medially and in the cranial region of the right lung medially; intermittent crepitations in the cranial region of the right lung medially; reduced thoracic expansion; and expiratory dyspnea. Pulmonary ultrasonography revealed hyperechogenic multifocal structures in both lungs. In view of the severe clinical condition and unfavorable prognosis, the owner opted for euthanasia. Necropsy revealed that there was a significant amount of yellow fluid in the thoracic cavity, and the cut surfaces of the lungs were covered with fibrin and pleural adhesions. The lungs had irregular surfaces with multifocal nodules of various sizes and firm consistency. The texture of the cut nodules was solid, and the nodules had a yellowish color. Histologically, the pulmonary nodules were composed of neoplastic cells. They were pleomorphic, infiltrative epithelial cells with little cytoplasm; large and spherical nuclei with abundant euchromatin; occasional anisokaryosis; visible nucleolus; and numerous mitotic figures. Results of anti-cytokeratin immunohistochemistry were strongly positive for cytokeratin in the lungs and lymph nodes. Discussion: The diagnosis of acinar pulmonary adenocarcinoma was based on clinical, laboratory, histopathological, and immunohistochemical findings. Clinical signs and lung ultrasound suggested a severe respiratory disease. Pulmonary tumors are usually solid, and they show areas of central necrosis that resemble granulomas. However, the histopathological findings in the current case were compatible with a primary pulmonary neoplasm. Primary pulmonary neoplasms, although rare, should be considered in the differential diagnosis of weight loss, cachexia, and respiratory symptoms in adult cattle. The morphological pattern and the strong immunoreactivity on immunohistochemical examination were conclusive for a diagnosis of a primary pulmonary adenocarcinoma of the acinar type because these tumors specifically contain cytokeratin.